Comparison of Pile Bearing Capacity Based on Standard Penetration Test (SPT), Hydraulic Static Pile Driven (HSPD), and Pile Driving Analyzer (PDA) Test in The Project of Flyover Antapani – Bandung - Retno Wulansari; Saihul Saihul Anwar (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2018)
ABSTRACTThe pile foundation is one of a kind of deep foundation that serves to funnel structural loads to hard soil layers that have a high carrying. The purpose of this study was to calculate the bearing capacity of piles.Based on SPT data obtained and calculated by Mayerhoff method at point BH-01 Qult = 259,992 tons, at point BH-02 Qult = 258,234 tons, and at point BH-03 Qult = 279.586 tons, with HSPD data obtained based on reading dial pressure manometer tool is approximately from 178,365 tons - 186,120 tons, whereas with PDA obtained based on RMX value on PDA test is about 124 tons - 225 tons.The results of the calculation of bearing capacity there are differences in values, both from the use of calculation methods and the location of points reviewed. From the results of the calculation can be concluded that the big highets bearing capacity the pile is values of SPT. In values of HSPD and PDA is relative same because the method using similar method (hydraulic and wave method).